597. Are We Dosing Correctly? Population Pharmacokinetic Modeling of Cefepime, Piperacillin-Tazobactam, and Meropenem in Individuals with Cystic Fibrosis. (15th December 2022) - Rolsma, Stephanie L; An, Guohua; Fishbane, Nick; Fissell, William; Gu, Kenan; Jimenez, Natalia; Kirkpatrick, Carl; Landersdorfer, Cornelia B; Nation, Roger L; Patel, Pratish C; Sokolow, Andrew G; Sokolow, Katherine; et al.
Abstract: Background: Patients with cystic fibrosis (CF) experience recurrent bacterial pulmonary exacerbations. The management of these infections becomes increasingly complex due to decreased antimicrobial susceptibility and inadequate pharmacokinetic/pharmacodynamic (PK/PD) characterization of the most commonly used antimicrobial agents in this population. Methods: One hundred fifty-five pediatric and adult participants receiving cefepime (n=82), meropenem (n=42), or piperacillin-tazobactam (n=31) were enrolled. Opportunistic blood samples were obtained during hospitalization. Population PK (PopPK) analysis was conducted using nonlinear mixed effects modeling in NONMEM, and clinical and demographic characteristics were evaluated as potential covariates. Monte Carlo simulations evaluated the probability of PK/PD target attainment (PTA) for different dosing regimens. Multiple targets, defined as percentage of a 24-h time period that the free drug concentration exceeds the MIC ( f T > MIC), were selected based on prior studies of beta-lactam antibiotics. Results: Preliminary PopPK modeling results show that lean body weight, creatinine clearance, daily dose, mode of administration (standard vs. extended infusion), and age affect PK parameters, with varying effects by drug. As anticipated, extended or continuous infusions resulted in higher PTA (Table 1). In the cefepime group, the 3-h infusion regimen achieved higher PTAs than the 0.5-h regimen across all age groups (Figure 1, Figure 2). Estimated breakpoints (in which ≥ 90% of patients are expected to achieve a PK/PD target) were 2-4 fold higher in pediatric participants receiving a 3-h infusion vs. 0.5-h infusion, based on age and target f T > MIC (Table 1). In the meropenem group, increased creatinine clearance led to reduced PTA, and in the piperacillin-tazobactam group, total daily dose and interval were the principal drivers of PTA. Table 1: Breakpoints (mg/L, highest minimum inhibitory concentration (MIC) with ≥ 90% PK target attainment) for different infusion durations, based on Monte Carlo simulations. Figure 1: Comparison of PTA between the two durations of infusion for 50 mg/kg (3 to 11 years) or 2 g (12 years and above) cefepime q8h at the target of 65% fT> MIC. Figure 2: Comparison of PTA between two durations of infusion for 50 mg/kg (3 to 11 years) or 2 g (12 years and above) cefepime q8h at the target of 100% fT> MIC. Conclusion: To our knowledge, this is the largest PopPK study to date of these antimicrobials in individuals with CF. Clinicians should incorporate local antibiograms with these PopPK models to determine optimal dosing in patients with CF, since standard dosing regimens may fail to achieve specific PK/PD targets. This population may also benefit from beta-lactam therapeutic drug monitoring. Disclosures: C. Buddy Creech, MD, MPH, Altimmune: Advisor/Consultant|Astellas: Advisor/Consultant|Merck: Grant/Research Support|Premier: Advisor/Consultant.